Improving the Text Writing of the Observation Report by Applying the STAD Model at the Seventh Grade of MTs Negeri 1 Kolaka - Agus Nasir (Journal of Indonesian Language Education and Literary, 2017)
This study aims to describe improvements in the ability to write text reports of observations through STAD model on the seventh grade students of MTs Negeri 1 Kolaka. The research design used is Classroom Action Research. The data of this research are the process data and learning result obtained through observation, test, and field notes. The data sources of this research are teachers and students. The results showed that the ability to write text reports of observations conducted by students can be improved through STAD model. The average value of pre-action test results, that is 66.97 and on the test cycle 1 the average value of student learning outcomes rose to 74.96. Similarly, in the second cycle test, the average value of students' learning outcomes rose to 81.41. Thus, it can be concluded that the ability to write text reports of observations can be improved through STAD model.